tsCRISPR based identification of Rab proteins required for the recycling of Drosophila TRPL ion channel - Zeger, Matthias; Stanisławczyk, Lena Sarah; Bulić, Marija; Binder, Andrea Maria; Huber, Armin (Frontiers in Cell and Developmental Biology, 2024)
In polarized cells, the precise regulation of protein transport to and from the plasma membrane is crucial to maintain cellular function. Dysregulation of intracellular protein transport in neurons can lead to neurodegenerative diseases such as Retinitis Pigmentosa, Alzheimer's and Parkinson's disease.Here we used the light-dependent transport of the TRPL (transient receptor potential-like) ion channel in Drosophila photoreceptor cells to study the role of Rab proteins in TRPL recycling. TRPL is located in the rhabdomeric membrane of dark-adapted flies, but it is transported out of the rhabdomere upon light exposure and localizes at the Endoplasmatic Reticulum within 12 hours. Upon subsequent dark adaptation, TRPL is recycled back to the rhabdomeric membrane within 90 minutes. To screen for Rab proteins involved in TRPL recycling, we established a tissue specific (ts) CRISPR/Cas9-mediated knock-out of individual Rab genes in Drosophila photoreceptors and assessed TRPL localization using an eGFP tagged TRPL protein in the intact eyes of these mutants. We observed severe TRPL recycling defects in the knockouts of Rab3, Rab4, Rab7, Rab32, and RabX2. Using immunohistochemistry, we further showed that Rab3 and RabX2 each play a significant role in TRPL recycling and also influence TRPL transport. We localized Rab3 to the late endosome in Drosophila photoreceptors and observed disruption of TRPL transport to the ER in Rab3 knock-out mutants. TRPL transport from the ER to the rhabdomere ensues from the trans-Golgi where RabX2 is located. We observed accumulated TRPL at the trans-Golgi in RabX2 knock-out mutants. In summary, our study reveals the requirement of specific Rab proteins for different steps of TRPL transport in photoreceptor cells and provides evidence for a unique retrograde recycling pathway of TRPL from the ER via the trans-Golgi.